Mapparola dalam Pernikahan Adat Suku Bugis di Sulawesi Selatan Perspektif Sosiologi Hukum Islam - Fitriyani, Fitriyani; Hendri, Hendri (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2024)
This study aims to analyze the mapparola tradition among the Bugis community from the perspective of Islamic Law sociology. The research addresses two questions: what the concept of mapparola in the wedding party of the Bugis tribe in Wajo is, and what are its implications from the perspective of Islamic Law sociology. This qualitative research employs field data collected through observation and interviews with community leaders and participants in the tradition. The data are analyzed using the ‘urf theory and the receptie a contrario theory, which emphasize that customary law can be valid as long as it does not contradict Islamic law. The findings indicate that the mapparola tradition in Bugis weddings is a form of respect towards the parents and families of the bride and groom, particularly the bride. This tradition, rich in social interactions and the exchange of various gifts, embodies strong Islamic legal philosophy. It is an extension of the guidance on dowry in Islamic law, sociologically shaped by the Bugis community's characteristic of sharing. However, mapparola sometimes poses challenges for prospective brides and grooms who may struggle to meet the traditional standards for providing the agreed-upon items. Therefore, this study recommends that the implementation of the mapparola tradition be adjusted to contemporary conditions, rationality, and the welfare of the prospective couples.